The challenge of interculturality - Casas Navarro, Raymundo (2006)
This essay reflects on interculturality from a critical perspective. In this way, it seeks to unravel the presuppositions in the discourse of interculturality and the network of conceptual relations at play. In this context, the notion of linguaculture is crucial to propose a new look at this pressing problem. The critical view of interculturality must start from the fact of recognizing that, as a truly existing state of affairs, interculturality has not fully crystallized in our country. However, the critical perspective that we defend does not fall into the swamp of inert pessimism, nor into hypocritical cynicism; rather, it can lead us, leaving aside self-deception, to a better state of affairs. In this sense, interculturality must be assumed as a project, a goal, a task, an agenda for the future. The true promise of Peruvian life lies in assuming the beautiful challenge of interculturality.